Temporary clogging effects induced by a sustainable anti-icing hydrogel on the hydraulic conductivity and inertia coefficient of open-graded asphalt pavements. (26th December 2022) - Autelitano, F.; Petrolo, D.; Chiapponi, L.; Giuliani, F.; Longo, S.
Abstract: Open-graded asphalt pavements require special winter maintenance procedures to ensure the effectiveness of anti-icing and deicing measures. A recently developed solution for this type of pavement is represented by an environmental friendly thickened bio-based salt hydrogel, which consists of a thermo-sensitive sodium chloride (NaCl) brine admixed with a gellant agent (seaweed fibers) having the ability to form a gel-like structure when hot-sprayed on a cold surface. This thin salt layer results in a long-lasting residual efficacy of the winter maintenance product and in a reduction of salt consumption, but affects the drainage capacity of the pavement. These transient clogging effects were evaluated on laboratory-made specimens through the measurement of their vertical hydraulic conductivity variations before and after the hydrogel application, using a 1-D air permeameter and a constant head water permeameter. The analyses, based on Darcy–Forchheimer model and Darcy model for lower Reynold numbers, revealed a significant short-term reduction of the hydraulic conductivity, that, anyway, tends to be almost totally restored once the critical weather event is over (after about 6 h).